Mechanical performance determinants in women`s vs men`s pole-vault - Cassirame, J.; Sanchez, H.; Homo, S.; Frère, J. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
Since its first world record in 1992 and its official introduction in 1999 at the 7th IAAF World Championships, the women`s pole vault event has been little studied. First data showed that, similarly to men, the run-up velocity could be considered as one of the main performance factors (Grabner 2004; McGinnis 2004). It has also been shown that performance in women`s pole vault was mainly explained by the energy of the athlete at the take-off and by the energy gain due to the work done by the athlete during the pole support phase (Grabner 2004; Schade et al. 2004). Although a higher angular momentum during the pole support phase has been found for women in comparison with men (Schade et al. 2004), the specificity of the women`s pole vault biomechanics with regard to the men remains an open question and is it not reasonable to consider that women`s performance are built similarly to men (Frère et al. 2010). This is all the more the case as the performance level in the women`s pole vault is still increasing. Therefore, the aim of this study was to determine for both women and men the relative influence of several take-off and pole support mechanical variables on the pole vault performance.